Arterial Stiffness and Incidence of Diabetes: A Population-Based Cohort Study - Muhammad, Iram Faqir; Borné, Yan; Östling, Gerd; Kennbäck, Cecilia; Gottsäter, Mikael; Persson, Margaretha; Nilsson, Peter M.; Engström, Gunnar (Diabetes care, 2017)
Diabetes is known to be associated with increased arterial stiffness. However, the temporal association between increased carotid-femoral pulse wave velocity (c-f PWV) and diabetes is unclear. The aim of this study is to explore the relationship between arterial stiffness, as determined by c-f PWV, and incidence of diabetes. The study population included participants from the Malmö Diet and Cancer cardiovascular cohort, using measurements from the 2007-2012 reexamination as baseline. Arterial stiffness was evaluated by measuring c-f PWV (SphygmoCor). After excluding participants with prevalent diabetes (according to measurements of fasting glucose, oral glucose tolerance tests, and physician's diagnoses), the final study population consisted of 2,450 individuals (mean age = 71.9 ± 5.6 years). Incidence of diabetes was followed by linkage to local and national diabetes registers. Cox proportional hazards regression was used to assess the incidence of diabetes in relation to the tertiles of c-f PWV, adjusted for potential confounders. During a mean follow-up of 4.43 ± 1.40 years, 68 (2.8%) participants developed diabetes. Crude incidence of diabetes (per 1,000 person-years) was 3.5, 5.7, and 9.5, respectively, for subjects in the first, second, and third tertiles of c-f PWV. After adjustment for potential confounders, the hazard ratio of diabetes was 1.00 (reference), 1.83 (95% CI 0.88-3.8), and 3.24 (95% CI 1.51-6.97), respectively, for the tertiles of c-f PWV ( for trend = 0.002). Increased c-f PWV is associated with increased incidence of diabetes, independent of other risk factors. These results suggest that increased arterial stiffness is an early risk marker for developing diabetes.